2020
DOI: 10.1093/ofid/ofaa152
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mortality in Patients With COVID-19: Clinical and Laboratory Parameters

Abstract: Background Several reports on epidemiological and clinical features of the 2019 coronavirus disease (COVID-19) have been published. However, mortality and morbidity analyses, important for better understanding the pathogenesis of this disease, are scarce. We examine the clinical and laboratory features of 14 patients who died of COVID-19. Methods The cohort consisted of 11 male and 3 female patients, with 9 patients aged 70 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
3
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 17 publications
5
27
3
7
Order By: Relevance
“…Independent risk factors associated with severe COVID-19 include male sex, increased age, and presence of comorbidities [ 6 , [8] , [9] , [10] , [36] , [37] , [38] ]. To evaluate whether the spatial distribution and abundance of ACE2 protein in the lower respiratory tract differed by these risk factors, we scored tissues for ACE2 protein detection ( Supplemental Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Independent risk factors associated with severe COVID-19 include male sex, increased age, and presence of comorbidities [ 6 , [8] , [9] , [10] , [36] , [37] , [38] ]. To evaluate whether the spatial distribution and abundance of ACE2 protein in the lower respiratory tract differed by these risk factors, we scored tissues for ACE2 protein detection ( Supplemental Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…15 Another study analyzing mortality revealed that 1 ($7%) out of 14 patients died due to GI bleeding. 16 It is worth noting, however, that the patient had lymphoma, thus comorbidities may represent a part of the risk profile.…”
Section: Bleeding and Bleeding Riskmentioning
confidence: 99%
“…Foi possível verificar neste estudo que a redução de linfócitos (linfocitopenia) foi a alteração laboratorial mais frequente, em consonância com descobertas da literatura (LU;FU et al, 2020;ZHENG et al, 2020;LI LONG-QUAN et al, 2020;TIAN et al, 2020;AGGARWAL et al, 2020;WEI et al, 2020;LI YANLEI et al, 2020), podendo ser utilizada como um índice de referência de diagnóstico clínico da COVID-19 (LI LONG-QUAN et al, 2020). A linfocitopenia pode ser explicada através de mecanismos distintos.…”
Section: Linfócitos Neutrófilos Leucócitos E Citocinasunclassified
“…A atrofia do tecido hematopoiético da medula óssea foi observada na SARS e na COVID-19 (TIAN et al, 2020). Segundo o tratamento com glicocorticóides pode induzir linfocitopenia em alguns pacientes (TIAN et al, 2020).…”
Section: Linfócitos Neutrófilos Leucócitos E Citocinasunclassified
See 1 more Smart Citation